A Computational Investigation into the Suitability of Purely Siliceous Zeolites as Reverse Osmosis Membranes - Hughes, Zak; Carrington, L.; Raiteri, Paolo; Gale, Julian (American Chemical Society, 2011)
Desalination by reverse osmosis is an increasingly important source of potable water in many countries. The interest in developing new, more effective membranes is, therefore, great. One set of materials that have been suggested as a possible new type of desalination membrane are nanoporous materials. In this work computational methods are used to investigate the behavior of water within five different zeolitic systems. Quantum mechanical calculations are used to construct a set of force-field parameters for two atomistic models. Molecular dynamics simulations of the zeolites show that water will diffuse through zeolites at a rate faster than that obtained with the composite membranes currently used in commercial desalination. In addition, the thermodynamics of salt rejection have been investigated using the free energy perturbation method. The results of these calculations show that the chloride ion finds the zeolitic environment strongly unfavorable compared to the bulk solution. In the case of the sodium ion, the energetic difference between the zeolite environment and solution is less significant, but charge separation prevents sodium from permeating the membrane.